PENGARUH KOMPETENSI DAN KOMITMEN PENYIDIK TERHADAP PENYELESAIAN KOMPLAIN KELUARGA/KORBAN DALAM PENANGANAN PERKARA OLEH ANGGOTA RESKRIM POLRES LAMPUNG UTARA - Agus Wantoro (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractThe aim of this research is to explore the influence of the competence and commitment of an investigators or an assistant investigator in the investigation process. The result shows that both of competence and commitment of an investigator or an assistant investigator have a significant relationship with the settlement of complaints. Competence has a strong enough influence with the resolution of complaints while the family has committed a weak influence on the family settlement of complaints/victims. Research findings indicate that the resolution of victim complaints will be good if the competence and commitment of investigators increased.